How Balkan Am I? Translation and Cultural Intimacy Through an Albanian-Greek Lens - Asimakoulas, Dimitris (Meta, 2016)
Historiographers, anthropologists and cultural studies experts have shown that discussions of identity in or about the Balkans have been traditionally linked to a sense of ‘deficiency.’ Given the history of conflict, the drive towards greater European integration and the effects of the current economic crisis in the region, there is an urgency to deconstruct such ideologies. This article shows how Herzfeld’s (2002; 2005) approach to Balkan marginality may be productively extended to cover cultural and translation critique. Thus his concept of cultural intimacy is applied to stories of migration. Two Greek works are examined: Gazmend Kapllani’s semi-autobiographic novel A Short Border Diary (2006), translated into English by Marie Stanton-Ife, and Filippos Tsitos’ film Plato’s Academy (2009), subtitled into English. Both works have set a precedent in terms of audience reception and as documents of a historical cycle, the migration of thousands of Albanians to Greece after the collapse of communism. Translation and subtitling into English respectively show that the written and the audiovisual medium present different opportunities for conveying Balkan otherness.